2016
DOI: 10.1177/1367877916636140
|View full text |Cite
|
Sign up to set email alerts
|

When passion isn’t enough: gender, affect and credibility in digital games design

Abstract: Design 2Recent controversies around identity and diversity in digital games culture indicate the heightened affective terrain for participants within this creative industry. While work in digital games production has been characterized as a form of passionate, affective labour, this paper examines its specificities as a constraining and enabling force. Affect, particularly passion, serves to render forms of game development oriented toward professionalization and support of the existing industry norms as credi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 24 publications
3
41
0
Order By: Relevance
“…Yet such findings are limited in their applicability, given their temporal boundedness and the diverse nature of participants, who are often not working professionals. Similarly those who have studied incubators and workshops that teach game design often focus on the politics of such programs [8], [9], rather than the discourses of the participants as they progressed. While valuable studies, such work is more focused on the structures that support developers rather than the developers themselves.…”
Section: Literature: Studying the Game Industrymentioning
confidence: 99%
“…Yet such findings are limited in their applicability, given their temporal boundedness and the diverse nature of participants, who are often not working professionals. Similarly those who have studied incubators and workshops that teach game design often focus on the politics of such programs [8], [9], rather than the discourses of the participants as they progressed. While valuable studies, such work is more focused on the structures that support developers rather than the developers themselves.…”
Section: Literature: Studying the Game Industrymentioning
confidence: 99%
“…To address the gap whereby the barriers to gameplay remain underexplored, I draw on the history of feminist game scholarship that has long illustrated that, although games are frequently marketed in a way that assumes they are of more interest to young boys (Burrill, 2008;Chess, 2017;Cote, 2018), in reality girls often are socialized away from gaming from a young age (de Castell & Bryson, 1998;Harvey, 2015). Interventionist feminist research has shown that when the entry conditions are changed (e.g., the creation of groups where girls can learn to play games in a girls-only environment or in women-led community groups focusing on mentoring other women through designing their own game), girls and women become active players and/or create their own games (Fisher & Harvey, 2013;Fisher, Jenson, & de Castell, 2015;Harvey, 2014;Harvey & Shepherd, 2017;Jenson & de Castell, 2011;Kafai, 2008). Beyond intentional feminist interventions, games directly marketed toward girls and women tend to be collaborative as opposed to competitive (Cunningham, 2018;Flanagan, 2005;Juul, 2010) or productive in nature (e.g., cognitive improvement games such as BrainAge) rather than play for play's sake (Chess, 2009(Chess, , 2010(Chess, , 2017.…”
Section: Barriers To Digital Gameplaymentioning
confidence: 99%
“…We have two main reasons, in this article. First, we aim to build on the work that has already been done on diversity initiatives in the games sector, notably the work of Alison Harvey, Stephanie Fisher and Tamara Shepherd (Harvey and Fisher 2015) (Harvey and Shepherd 2017) (Harvey and Fisher 2013) (Fisher and Harvey 2013). This work makes a strong case for such initiatives, whilst also highlighting the tensions they sustain, notably between aims and process.…”
Section: Introductionmentioning
confidence: 99%